A simulation of swage process for hard disk drive factory based on explicit dynamics analysis - Watchara Bubpatha; Jatuporn Thongsri (2022 37th International Technical Conference on Circuits/Systems, Computers and Communications (ITC-CSCC), 2022)
Nowadays, the hard disk drive (HDD) industry is very competitive and focuses on enhancing the performance and capacity of HDD. To serve these purposes, HDD manufacturers prefer to increase the number of media, thus adding more head gimbal assemblies (HGAs) as well. A swage process (SP) assembles between HGAs and arm actuators into a head stack assembly (HSA). The greater the number of HGAs, the thinner it gets. Such thinness in some products, after passing the SP, there could be higher deformation and stress in arm actuators than expected values. To investigate and understand this problem. This article proposes an explicit dynamic analysis (EDA) in ANSYS software to solve the problem and simulate the SP using an actual condition from a manufacturer. The EDA provides simulation results that are consistent with the experimental results. The analytical results lead to understanding the SP's deformation, strain, and lubricant effect. Therefore, the EDS is a precise and appropriate method for developing the SP in the HDD manufacturing process.
Keywords: Energy Efficiency and Management; Advanced Control Systems Optimization; Industrial Automation and Control Systems